PENGARUH PENERAPAN MODEL PEMBELAJARAN LAPS (LOGAN AVENUE PROBLEM SOLVING) – HEURISTIC TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN KEMAMPUAN KONEKSI MATEMATIKA PESERTA DIDIK KELAS VII SMP SANTO YOSEPH DENPASAR TAHUN PELAJARAN 2018/2019 - I Made Surat (Emasains : Jurnal Edukasi Matematika dan Sains, 2021)
This study aims to determine the effect of the application of the LAPS (Logan Avenue Problem Solving) - Heuristic learning model on the problem solving abilities and mathematical connection skills of seventh grade students of SMP Santo Yoseph Denpasar in the 2018/2019 academic year.This type of research is a quasi-experimental research with a Non-Equivalent Post Test-Only Control Group Design research design. The population in this study were all students of class VII SMP Santo Yoseph Denpasar for the 2018/2019 academic year consisting of 9 classes of 309 people. Of the 9 classes, 2 classes were selected as samples, namely the experimental class (VII A) and the control class (VII D) which were taken randomly using the Multistage Random Sampling technique. The data collected in this study used a test method, namely a problem-solving ability test and a mathematical connection ability test. Data analysis in this study used Manova. Based on the results of data analysis, it is obtained: 1) There are differences in problem-solving abilities between students who follow the LAPS-Heuristic learning model and students who follow conventional learning models. 2) There are differences in the ability of mathematical connections between students who follow the LAPS-Heuristic learning model and students who follow conventional learning models. 3) There are simultaneous differences in problem-solving abilities and mathematical connection abilities between students who follow the LAPS-Heuristic learning model and students who follow conventional learning models. Based on the results of testing the three hypotheses above, it can be concluded that the application of the LAPS-Heuristic learning model has a positive effect on the problem-solving abilities and mathematical connection abilities of seventh grade students of SMP Santo Yoseph Denpsar in the 2018/2019 academic year.